STRATEGI PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KESEJAHTERAAN DI ERA DIGITAL - Wita Hariani; Yohanes Susanto (SENGKUNI Journal (Social Science and Humanities Studies), 2026)
This study aims to analyze community empowerment strategies in improving social welfare in the digital era. The rapid development of information technology has brought significant changes in various aspects of life, including efforts to enhance community welfare. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, field observations, and documentation studies involving community members and relevant stakeholders. The findings indicate that digital-based community empowerment strategies, such as digital literacy training, the use of social media for business development, and assistance provided by social workers, are able to improve access to information, economic opportunities, and social participation. However, the implementation of these programs still faces several challenges, including low levels of digital literacy, limited technological infrastructure, and insufficient sustainable assistance. Therefore, synergy among the government, social institutions, and the community is essential in designing and implementing inclusive and sustainable empowerment programs. With appropriate strategies, digital-based community empowerment is expected to become an effective solution for improving social welfare more equitably in the digital era.